(untitled) - Muramatsu, Teijiro (Japan, 1968)
This book introduce about mathmatics, the solid foundation, dawn of the electic age, electric power for growing industries, two thousand years of shipbuiding...
Keywords: Technological innovations,Đổi mới công nghệ; History,Lịch sử; Japan,Japan